Comparação do efeito imediato da retroalimentação auditiva atrasada, mascarada e amplificada na fala de gagos e de não gagos - Fiorin, Michele [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The literature shows the advance and the increase of the interest in the investigation of the effects of altered auditory feedback on the speech of people who stutter. However, there still isn't consensus about the criteria of indication and the effect of the use of delayed (DAF), masked (MAF) and amplified (AmAF) auditory feedback.Thus, the purpose of this study was to compare the immediate effects of modification in the hearing regarding the frequency of disfluency and speech rate of spontaneous speech in people who stutter and people who do not stutter, using delay, masking and amplification. Participants were 32 individuals from eight to seventeen years and eleven months, divided into four groups: moderate stuttering group (Experimental Group 1 - EG1) composed by eight people with moderate stuttering; severe stuttering group (Experimental Group 2 - EG2) consisted of eight people with severe stuttering; group of fluent (Control Group 1 - CG1) consisted of eight people without stuttering matched to EG1, and; group of fluent (Control Group 2 - CG2) consisted of eight people without stuttering matched the EG2. The participants of EG showed at least 3% of stuttering-like disfluencies (SLD), eight of them showed stuttering classified as moderate, and other eight, severe stuttering, according to the Stuttering Severity Instrument (SSI-3). The following procedures were performed: audiology assessment, fluency assessment in four listening conditions, the non-altered auditory feedback, delayed (DAF), masked (MAF) and amplified (AmAF) and application of the Stuttering Severity Instrument (SSI-3) for participants of EG. The Fono Tools software was used to cause the effects of DAF, MAF and AmAF. Statistical analysis was performed with data from the Wilcoxon signed rank test for intra-group analysis, and the Mann-Whitney test for intergroup analysis. The results showed that the DAF provided decrease of stuttering-like disfluency in severe ...

A literatura mostra o avanço e o aumento do interesse nas investigações dos efeitos das alterações da retroalimentação auditiva em pessoas com gagueira. No entanto, ainda não há um consenso sobre os critérios de indicação e o efeito do uso da retroalimentação auditiva atrasada (RAA), mascarada (RAM) e amplificada (RAAm). Portanto, o objetivo deste estudo foi comparar os efeitos imediatos da modificação da escuta auditiva com relação à frequência das disfluências e taxa de elocução da fala espontânea em pessoas com e sem gagueira, utilizando-se atraso, mascaramento e amplificação auditiva. Participaram 32 indivíduos de oito a dezessete anos e onze meses, divididos em quatro grupos: grupo de gagueira moderada (Grupo Experimental 1 - GE1), composto por oito pessoas com gagueira moderada; grupo de gagueira grave (Grupo Experimental 2 - GE2), composto por oito pessoas com gagueira grave; grupo de fluentes (Grupo Controle 1 - GC1), composto por oito pessoas sem gagueira pareadas ao GE1; e grupo de fluentes (Grupo Controle 2 - GC2), composto por oito pessoas sem gagueira pareadas ao GE2. Os participantes dos GE apresentaram o mínimo de 3% de disfluências típicas da gagueira, sendo que oito deles apresentaram gagueira classificada como moderada, e oito, gagueira grave de acordo com o Instrumento de Gravidade da Gagueira (Stuttering Severity Instrument-SSI-3). Foram realizados os seguintes procedimentos: avaliação audiológica, avaliação da fluência, em quatro condições de escuta, a saber, retroalimentação auditiva habitual (RAH), atrasada (RAA), mascarada (RAM) e amplificada (RAAm), e aplicação do Instrumento de Gravidade da Gagueira para os participantes do GE. O software Fono Tools foi utilizado para provocar os efeitos da RAA, RAM e RAAm. Foi realizada análise estatística dos dados com o teste dos Postos Sinalizados de Wilcoxon para análise intragrupos e o teste de Mann-Whitney ...
Keywords: Fonoaudiologia; Fala; Disturbios da fala; Gagueira; Audição (Fisiologia); Speech